Assessment of Geothermal Potentials In Some Parts of Upper Benue Trough Northeast Nigeria Using Aeromagnetic Data - Mohammed, Abdulwahab; Adewumi, Taiwo; Kazeem, Salako Adeyinka; Abdulwaheed, Rafiu; Adetona, Abbass Adebayo; Usman, Alhassan (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
The assessment of geothermal potentials over part of the upper Benue trough corresponding to Kaltungo, Guyok, Lau and Dong areas, North Eastern Nigeria using spectral depth analysis of aeromagnetic data has been carried out. The study area is bounded by latitudes 9o00’N and 10o00’N and longitudes 11o00’E and 12o00’E. This research work is necessitated by the need for renewable and alternative sources of energy for use in Nigeria. Regional/residual separation was carried out on the total magnetic field using polynomial fitting method of order one. The residual map was divided into nine overlapping blocks for the spectral analysis. The centroid depths and depth to top of basement were obtained from the plot of log of power spectrum against wavenumber. These two parameters were used to estimate the Curie point depth using , where    and  are Curie depth, centroid depth and depth to top of basement respectively. The results from the spectral analysis suggested that in the parts of the Upper Benue trough, the basement is deepest at the south western portion towards the Lau area and varies between 0.55 and 3.8 km, while the centroid depth varies from 7.26 to 18.00 km. From the same portion of the trough, the Curie-point depths vary between 12.43 and 33.91 km and the corresponding geothermal gradient and heat flow values varying from 17.10 to 46.66 0C/km with an average of 30.75 0C/km and 42.75 to 116.65 mW/m2 with an average of 75.91 mW/m2 respectively. The maximum heat flow is found around the south western portion of the study area (Lau). The entire study area with high heat flow values might probably be good sources for geothermal and thereby recommended for both geothermal exploration and exploitation.